Analisis Penegakan Hukum Tindak Pidana Pencabulan Terhadap Anak Dibawah Umur (Studi di Unit PPA Polrestabes Medan) - Dosma Pandapotan; Syafruddin Kalo; Marlina Marlina; Edi Yunara (Universitas Sumatera Utara, 2022)
English translation. Obscenity against a child is a criminal offense that attacks the honor of the child's decency. The problems and objectives of this study are to find out the form and factors causing the criminal act of child molestation in the PPA Unit of the Medan Police; know the process of handling child molestation crimes by the PPA Unit of the Medan Police: knowing the obstacles and efforts of the PPA Unit in enforcing the law on child molestation crimes in the jurisdiction of the Medan Police. The research method carried out is a normative juridical research method. This study resulted in the conclusion that the form of child molestation in the PPA Unit of the Medan Police is generally an act of copulation by both child abusers and adult perpetrators. Obstacles to law enforcement of criminal acts of child molestation by the PPA Unit in terms of witnesses to criminal acts and finding perpetrators. So efforts were made such as conducting Visum et Revertum to victims and publishing a People Search List (DPO).